Understanding of decreased sialylation of Fc‐fusion protein in hyperosmotic recombinant Chinese hamster ovary cell culture: N‐glycosylation gene expression and N‐linked glycan antennary profile. Issue 8 (30th March 2017) - Lee, Jong Hyun; Jeong, Yeong Ran; Kim, Yeon‐Gu; Lee, Gyun Min
ABSTRACT: To understand the effects of hyperosmolality on protein glycosylation, recombinant Chinese hamster ovary (rCHO) cells producing the Fc‐fusion protein were cultivated in hyperosmolar medium resulting from adding NaCl (415 mOsm/kg). The hyperosmotic culture showed increased specific Fc‐fusion protein productivity ( q Fc ) but a decreased proportion of acidic isoforms and sialic acid content of the Fc‐fusion protein. The intracellular and extracellular sialidase activities in the hyperosmotic cultures were similar to those in the control culture (314 mOsm/kg), indicating that reduced sialylation of Fc‐fusion protein at hyperosmolality was not due to elevated sialidase activity. Expression of 52 N ‐glycosylation‐related genes was assessed by the NanoString nCounter system, which provides a direct digital readout using custom‐designed color‐coded probes. After 3 days of hyperosmotic culture, nine genes ( ugp, slc35a3, slc35d2, gcs1, manea, mgat2, mgat5b, b4galt3, and b4galt4 ) were differentially expressed over 1.5‐fold of the control, and all these genes were down‐regulated. N ‐linked glycan analysis by anion exchange and hydrophilic interaction HPLC showed that the proportion of highly sialylated (di‐, tri‐, tetra‐) and tetra‐antennary N ‐linked glycans was significantly decreased upon hyperosmotic culture. Addition of betaine, an osmoprotectant, to the hyperosmotic culture significantly increased the proportion of highly sialylated and tetra‐antennary N ‐linked glycans ( P  ≤ 0.05), while it increased the expression of the N ‐glycan branching/antennary genes ( mgat2 and mgat4b ). Thus, decreased expression of the genes with roles in the N ‐glycan biosynthesis pathway correlated with reduced sialic acid content of Fc‐fusion protein caused by hyperosmolar conditions. Taken together, the results obtained in this study provide a better understanding of the detrimental effects of hyperosmolality on N ‐glycosylation, especially sialylation, in rCHO cells. Biotechnol. Bioeng. 2017;114: 1721–1732. © 2017 Wiley Periodicals, Inc. Abstract : Hyperosmolality often negatively affects protein glycosylation in recombinant CHO (rCHO) cells. This study provides a better understanding of the detrimental effects of hyperosmolallity on sialylation of Fc‐fusion protein in rCHO cells. Hyperosmolality decreased the sialylation of recombinant proteins through reducing the highly sialylated and tetra‐antennary N ‐linked glycans.